ECCO Position on Harmonisation of Crohn's Disease Mucosal Histopathology. (11th January 2022) - Magro, F; Sabino, J; Rosini, F; Tripathi, M; Borralho, P; Baldin, P; Danese, S; Driessen, A; Gordon, I O; Iacucci, M; Noor, N; Svrcek, M; et al.
Abstract: In inflammatory bowel disease [IBD], mucosal healing is a major therapeutic target and a reliable predictor of clinical course. However, endoscopic mucosal healing is not synonymous with histological healing, and the additional benefits of including histological remission as a target are unclear. In Crohn´s disease [CD], there are few studies highlighting the value of histological remission as a therapeutic target. Histological activity can persist in CD patients who are in endoscopic remission, and the absence of histological activity may be associated with lower relapse rates. Therefore, standardisation of procedures to evaluate CD histological activity is desirable. Topics that would benefit from standardisation and harmonisation include biopsy procedures, biopsy processing techniques, the content of histological scores, and the definitions of histological remission, histological response, and histological activity. In line with these needs, the European Crohn's and Colitis Organisation [ECCO] assembled a consensus group with the objective of developing position statements on CD histology based on published evidence and expert consensus. There was agreement that definitions of histological remission should include absence of erosion, ulceration, and mucosal neutrophils; that the absence of neutrophilic inflammation is an appropriate histological target in CD; that CD histological scores, such as the Global Histological Disease Activity Score, lack formal validation; and that histological scoring systems for ulcerative colitis, including the Geboes Score, Robarts Histopathology Index, and Nancy Histological Index, can be used for scoring intestinal biopsies in CD patients.